A simple model of wastewater treatment plants for managing the quality of the Seine River. Issue 18 (2018) - Robles-Rodriguez, C.E.; Bernier, J.; Rocher, V.; Dochain, D.
Abstract: The aim of this paper is to introduce a simple model for wastewater treatment plants that can be used for evaluating control strategies on the basin of the Seine River under different scenarios. The model represents a bioreactor without oxygen limitation. The construction of the model was based on the ASM1 with only one microbial population. The performance of the model was tested on daily data for a four year period over the three main wastewater treatment plants of the Seine River in Paris (Seine Aval, Seine Centre, and Seine Grésillons). Results demonstrated that the model was effective for predicting the concentrations of ammonia, nitrites, nitrates, biological oxygen demand, and total suspended solids. The developed model was found to be parsimonious and it can thus provide a useful tool in optimizing river quality once coupled to control strategies.